Population genetics and incidence of hybridization in the rare Colorado endemic plant Physaria bellii - Kothera, Linda, author; Detling, James K., advisor (Colorado State University. Libraries, 2006)
Physaria bellii Mulligan (Brassicaceae) is a rare, herbaceous perennial endemic to shale and sandstone outcrops along the Front Range of northern Colorado, USA. Leaves were collected for genetic and morphological analyses from a sample of 10 P. bellii, 11 P. vitulifera Rydberg and two putative hybrid populations. The first part of the study estimated genetic diversity and structure of P. bellii populations using ISSR (Inter-Simple Sequence Repeat) markers. Genetic diversity of P. bellii populations was moderate (expected heterozygosity = 0.22), and a moderately high degree of population structure was found (FST ranged from 0.17 - 0.24). After dividing populations into a northern (populations 1-5) and a southern (populations 6-10) group, a hierarchical AMOVA partitioned most of the variation among individuals within populations (74%), with lesser amounts among populations within groups (20%) and between groups (6%). An analysis of genotypes suggests that gene flow is occurring among the southern P. bellii populations such that the ten sampled populations were grouped into eight genetic clusters. A Mantel test of the correlation between genetic and geographic distances was highly significant (p < 0.001), suggesting a clinal pattern of variation. In the second part of the study, genetic data from ISSR markers established that putative hybrids should be classified as such. The distribution of species-diagnostic markers in hybrids, including a small number of known FI individuals, suggests that the natural hybrid populations are genetically more similar to P. vitulifera than P. bellii. Morphological data from leaf measurements showed hybrids to be intermediate for three of five characters. Morphological data supported the genetic data with Canonical Discriminant Analyses of both data sets showing similar patterns. Further assessments to examine whether P. bellii was threatened by hybridization with P. vitulifera included using root tip chromosome squashes to determine ploidy levels of P. vitulifera populations in proximity to P. bellii populations, and performing controlled interspecific and intraspecific crosses. The results indicate P. bellii is not currently threatened by hybridization with P. vitulifera, and efforts to conserve P. bellii should focus on the threat from potential habitat loss instead of from hybridization.
Keywords: botany